Microbial enzymatic assays in environmental water samples: Impact of inner filter effect and substrate concentrations. (21st October 2020) - Urvoy, Marion; Labry, Claire; Delmas, Daniel; Creac'h, Layla; L'Helguen, Stéphane
Abstract: As microbial enzymatic activities initiate the mineralization of organic matter through the microbial loop, it is important to correctly measure those activities and be able to perform inter‐study comparisons. Enzymatic activity assays are typically carried out using fluorogenic substrate analogs, such as 4‐methylumbelliferone and 7‐amino‐4‐methylcoumarin linked to sugar monomers, phosphate group, or amino acids. However, methodological divergences can be found in aquatic science literature, potentially leading to misestimated activities. To highlight some of those methodological key points, we first addressed the potential occurrence of an inner filter effect (IFE), a fluorometric artifact that affects the relationship between fluorophore concentration and fluorescence intensity, due to absorption of exciting or emitted light. It has never been considered in the context of environmental water studies before, despite significantly affecting measured activities. IFE occurred with two out of three tested spectrofluorometers when assaying proteases, although no IFE was detected for phosphatase assays. We also evaluated how substrate concentration ranges might affect kinetic parameters estimation, revealing that a many existing studies might use insufficient maximum substrate concentration. Finally, for single substrate concentration assays, we argued for the use of saturating substrate concentration, as naturally occurring substrates might compete with the fluorogenic analog at trace level. The amendment of a molecule mimicking natural substrates generated a significant inhibition of natural seawater phosphatases and proteases assayed with trace concentrations of fluorogenic substrate, while almost no inhibition occurred at higher concentrations. Those key points need to be addressed in order to assess enzymatic rates and allow inter‐study comparison.